The Effect of Industrial and Domestic Waste Pollution on Reservoir Water Quality - Hariyadi, Rosyid (Universitas Pakuan, 2023)
Duriangkang Reservoir is located in the Duriangkang River Basin, Batam Island. The main problem of Duriangkang Reservoir is that industrial wastewater from the Batamindo Industrial Area has been heavily polluted with COD levels (134.61 mg/liter) exceeding the Wastewater Quality Standards for Class II (80 mg/liter), domestic wastewater from domestic activities in the Duriangkang Watershed has also been heavily polluted with BOD5 levels (58.22 mg/liter) exceeding the Wastewater Quality Standards for Class II (50 mg/liter). This study aims to examine the effect of industrial wastewater and domestic wastewater on the carrying capacity of Duriangkang Reservoir. The main function of Duriangkang Reservoir is as a water resource to support 78% of the drinking water supply needs of Batam Island with a processing capacity of 3000 liters/second.